Implementation of the Team Games Tournament (TGT) Cooperative Learning Model to Improve Reading and Comprehension Skills of Wayang Stories - Rahman, Awening Wulan Nurhana; Suharni, Sri; Purnomo, Sucipto Hadi (Universitas PGRI Semarang, 2024)
This research was motivated by students' poor understanding of wayang story material in class VIII A at SMP Negeri 13 Semarang. This is caused by the lack of distribution of Javanese vocabulary used in wayang stories. This research aims to apply the Team Games Tournament (TGT) type cooperative learning model to improve the reading comprehension skills of class VIII A students at SMP Negeri 13 Semarang. The research method used is classroom action research (PTK) Kemimis and McTaggart models. The research subjects were students in class VIII A of SMP Negeri 13 Semarang. There were two data collection techniques used, namely test and non-test. Non-written collection took the form of an interview and written observations using a pretest-posttest. The pretest score is carried out once in pre-cycle activities, and the posttest is carried out twice at the end of each cycle. Quantitative analysis uses Excel to calculate changes through numbers. The results of this research show that in pre-action, the students' average score was 37.41, in cycle I, there was an increase with an average score of 80 and in cycle II, there was another increase of 92.65, so it can be concluded that learning wayang stories uses the Team Games type cooperative learning model. Tournament (TGT) can improve the reading comprehension skills of class VIII A students at SMP Negeri 13 Semarang.